Predictors of smoking cessation: A longitudinal study in a large cohort of smokers - Holm, Mathias; Schiöler, Linus; Andersson, Eva; Forsberg, Bertil; Gislason, Thorarinn; Janson, Christer; Jogi, Rain; Schlünssen, Vivi; Svanes, Cecilie; Torén, Kjell (Respiratory medicine, 2017)
There are few studies on predictors of smoking cessation in general populations. We studied the smoking cessation rate in relation to several potential predictors, with special focus on respiratory and cardiovascular disease. Smokers (n = 4636) from seven centres in Northern Europe, born between 1945 and 1973, who answered a questionnaire in 1999–2001 (the RHINE study) were followed up with a new questionnaire in 2010–2012. Altogether 2564 answered the questionnaire and provided complete data on smoking. Cox regression analyses were performed to calculate hazard ratios (HRs). A total of 999 subjects (39%) stopped smoking during the study period. The smoking cessation rate was 44.9/1000 person-years. Smoking cessation was more common with increasing age, higher education and fewer years of smoking. Asthma, wheeze, hay fever, chronic bronchitis, diabetes and hypertension did not significantly predict smoking cessation, but smokers hospitalized for ischaemic heart disease during the study period were more prone to stopping smoking (HR 3.75 [2.62–5.37]). Successful smoking cessation is common in middle-aged smokers, and is associated with few smoking years and higher education. A diagnosis of respiratory disease does not appear to motivate people to quit smoking, nor do known cardiovascular risk factors; however, an acute episode of ischaemic heart disease encouraged smoking cessation in our study population. •Successful smoking cessation is common in middle-aged smokers in Northern Europe.•An acute ischaemic heart disease event is a strong predictor for smoking cessation.•Respiratory disease or known cardiovascular risk factors do not favour smoking cessation.•Few smoking years and higher education are both predictors of smoking cessation.